Framing and Discourse Analysis of Indonesian Democracy: A Study of International Media News on the Figure of Prabowo Subianto - Muhammad Akram Mursalim; Intan Tiara Kartika; Citra F.I.L Dano Putri (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
This research aims to identify the framing pattern of international media on President Prabowo Subianto in the context of Indonesian democracy and to analyze the construction of democratic discourse in international news coverage. This study uses a qualitative approach by combining Entman's Framing Analysis and Fairclough's Critical Discourse Analysis (CDA). Data were collected from five reputable international media outlets—The Guardian, The New York Times, BBC News, Al Jazeera, and The Washington Post—through online documentation using specific keywords. The analysis was conducted using NVivo software to organize the data into three main categories: framing, democratic discourse, and personal narratives. The findings show that negative framing is the dominant pattern, accompanied by political and responsibility frames that highlight Prabowo's role as a political actor with substantial influence on the direction of Indonesian democracy. In the democratic discourse dimension, the two main axes are authoritarianism and democratic values, supported by issues of election integrity and human rights. The personal narrative emphasizes Prabowo's controversial past, military background, and populist rhetoric, while temporal analysis shows shifts in issue emphasis across the pre-election, transition of power, and early governance phases. The word-cloud visualization confirms the interconnection between personal narratives, democratic frameworks, and human rights issues. The study concludes that international media construct Prabowo's image as a complex political figure, combining strong-leadership appeal with skepticism toward democratic commitment. Theoretically, this study demonstrates how the integration of Entman's framing functions and Fairclough's three-dimensional CDA advances the understanding of leaderisation in emerging democracies, where personal leadership images are constructed through media selection, ideological discourse, and global democratic norms.